1998
DOI: 10.1183/09031936.98.11010133
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide anion production by monocytes of corticosteroid-treated asthmatic patients

Abstract: Bronchial asthma is a chronic inflammatory disease of the airways characterized by an increased recruitment of inflammatory cells, including mononuclear phagocytic cells such as monocytes [1]. The ability of these cells to generate highly reactive oxygen species (ROS), including super-oxide anion, following activation of a membraneassociated reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase is an important part of the host defence system, and has also been implicated in inflammation in a vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 33 publications
1
22
1
3
Order By: Relevance
“…Previous studies have shown that treatment with corticosteroids reduces oxidative stress and restores intracellular SOD activity levels in mild asthma [28,29]. In our study, no correlation between inhaled steroids and SOD activity was found and complements the findings of a previous study [15], thus making it less likely that inhaled steroids influence SOD activity.…”
Section: Discussionsupporting
confidence: 84%
“…Previous studies have shown that treatment with corticosteroids reduces oxidative stress and restores intracellular SOD activity levels in mild asthma [28,29]. In our study, no correlation between inhaled steroids and SOD activity was found and complements the findings of a previous study [15], thus making it less likely that inhaled steroids influence SOD activity.…”
Section: Discussionsupporting
confidence: 84%
“…Whole cell-binding assay PBM were isolated from blood by centrifugation over isotonic Percoll solutions (Pharmacia, St. Quentin en Yvelines, France) as described previously [11]. Cell viability and number were determined using the trypan blue exclusion test.…”
Section: Subjectsmentioning
confidence: 99%
“…These studies were reproduced in large animals, where it was demonstrated that oxygen radicals contribute to Ag-induced airway hyperreactivity (35,36). In addition, neutrophils and mononuclear cells generate proportionately more O 2 Ϫ ⅐ and H 2 O 2 in the lungs of asthmatics compared with healthy controls (32,34). ROS generation also correlates with increased airway hyperreactivity in asthmatic lungs (31,33).…”
mentioning
confidence: 99%